In Support of the TRIPS Agreement - JAKOBSSON, Amanda (Institutional Knowledge at Singapore Management University, 2012)
This paper challenges the conventional wisdom that the TRIPs agreement is bad for developing countries. We present a dynamic general equilibrium model of North-South trade that allows us to study the implications of stronger intellectual property rights (IPR) protection and simultaneous trade liberalization. In our model, stronger IPR protection in the South (TRIPs) leads to more innovation in the North, more technology transfer to the South and higher long-run southern consumer welfare. The South also benefits from trade liberalization but the welfare gains from TRIPs are considerably larger.